1996
DOI: 10.1183/09031936.96.09010100
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nebulized glycopyrrolate and metaproterenol in chronic obstructive pulmonary disease

Abstract: We assessed the bronchodilating effect of glycopyrrolate (GP) and compared it with that of metaproterenol (MP), alone and in combination (GP+MP), in patients with chronic obstructive pulmonary disease (COPD).In a double-blind study, 11 patients (aged (mean±SD) 69±6 yrs; forced expiratory volume in one second (FEV1) 1.2±0.4 L) with stable COPD inhaled nebulized GP 1.0 mg, MP 15 mg, or GP 1.0 mg + MP 15 mg. Spirometry was performed before inhalation and at hourly intervals for 8 h after inhalation.It was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In normal subjects, glycopyrrolate produces significant bronchodilation of long duration ( Gal & Suratt, 1981 ; Gal et al ., 1984 ). In patients with chronic obstructive pulmonary disease, inhaled nebulized glycopyrrolate (1 mg) produced a bronchodilating effect that lasted for 8 h ( Tzelepis et al ., 1996 ). Similarly, in patients with asthma, when compared to placebo, metered‐dose aerosols of glycopyrrolate (doses ranging from 100–1200 mg) elicited significantly greater bronchodilation that was noted within 30 min of dosing and was sustained for at least 8–12 h ( Walker et al ., 1987 ; Schroeckenstein et al ., 1988 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In normal subjects, glycopyrrolate produces significant bronchodilation of long duration ( Gal & Suratt, 1981 ; Gal et al ., 1984 ). In patients with chronic obstructive pulmonary disease, inhaled nebulized glycopyrrolate (1 mg) produced a bronchodilating effect that lasted for 8 h ( Tzelepis et al ., 1996 ). Similarly, in patients with asthma, when compared to placebo, metered‐dose aerosols of glycopyrrolate (doses ranging from 100–1200 mg) elicited significantly greater bronchodilation that was noted within 30 min of dosing and was sustained for at least 8–12 h ( Walker et al ., 1987 ; Schroeckenstein et al ., 1988 ).…”
Section: Discussionmentioning
confidence: 99%
“…Glycopyrrolate, a quaternary ammonium compound, is a muscarinic receptor antagonist which has been used in pre‐anaesthetic medication to reduce gastric acid and salivary secretions or to reverse neuromuscular blockade ( Norgaard et al ., 1970 ; Mirakhur & Dundee, 1983 ). Recently, glycopyrrolate has been used as a bronchodilator in patients with asthma and COPD ( Walker et al ., 1987 ; Gilman et al ., 1990 ; Tzelepis et al ., 1996 ). In this study we have investigated the potency and duration of action of glycopyrrolate in inhibiting cholinergic contractile responses evoked by electrical field stimulation (EFS) in guinea‐pig, and human airways.…”
Section: Introductionmentioning
confidence: 99%
“…Inhaled glycopyrronium causes long-lasting bronchodilation in patients with COPD. 18 The major metabolic pathway of glycopyrronium involves hydroxylation of the cyclopentyl ring and oxidation of the hydroxyl group in the mandelic acid residue. 19 However, most (80%) of intravenously administered glycopyrronium is excreted unmetabolized in humans.…”
mentioning
confidence: 99%
“…In the 1980s, the compound became of interest for the treatment of respiratory conditions when several pilot studies showed that inhaled glycopyrrolate (0.1-1.2 mg) displayed 8-12 h bronchodilatory activity in asthma and COPD patients [38][39][40]. The pharmacology of racemic glycopyrrolate was also characterized and compared with ipratropium bromide in guinea pig and human airways [41]. This evaluation showed that the compound displayed high affinity and no selectivity in its binding to the M 1 -M 3 receptors (K i values of 0.5-3.6 nM).…”
Section: Glycopyrrolatementioning
confidence: 98%